A comparative machinability study on titanium alloy Ti-6Al-4V during dry turning by cryogenic treated and untreated condition of uncoated WC inserts. (2020) - Kumar, Upendra; Senthil, P.
Abstract: Titanium alloy is widely utilized in aerospace, nuclear power plant and medical applications due to its high hardness, corrosion resistance, specific strength and bio-compatibility. Titanium alloys are tough to machine because of its intrinsic properties such as the capability to maintain high strength at elevated temperatures, high hardness and low thermal conductivity. Moreover, titanium alloys lower thermal conductivity and high specific heat limit the effective removal of heat developed during machining through workpiece and chips. Thus it accumulates at the cutting zone. Present work deals with a comparative study on surface roughness, cutting force, and chip morphology during turning of Titanium alloy Ti-6Al-4V alloy with and without cryogenic treated uncoated tungsten carbide inserts. The cutting force and surface roughness resulting from machining with cryogenically treated inserts are comparatively lesser than machining with untreated inserts. This is due to more hardness, low thermal conductivity and high wear resistance of treated inserts.